The Beetle Assemblage of Langkawi Island - Abdulah, Fauziah (Malaysian Journal of Science, 2005)
A study of the beetle assemblage was conducted at the forest reserves at Lubok Semilang, Telaga Tujoh, Datai, Durian Perangin, Kisap, Tetrogona forest plantation at Sawak Hill and the base camp at Burau Bay, Langkawi Island. 835 beetles from 201 species and 23 families were sampled using net sweeping, leaf litter collection, pitfall traps, Malaise trap and light trapping. The Simpson index of diversity was 39.44 and Margalef index of abundance was 29.73. Staphylinidae was the most diverse beetle family with Scarabaeidae being the most abundant. Light trapping was most efficient collecting 48% (n=415) of the total number of beetles collected. The maximum number of species of beetles collected was from Lubok Semilang (84 species). Light trapping at Telaga Tujoh collected high diversity of beetles (Simpson index=22.05). Thus far 67 species of beetles have been identified to species level. New records for Langkawi are Acceralus laevicollis, 4 species of Acerida spp., Apogonia spp., Copris doriae, Aserid spp., Onthophagus rugicolis, Onthophagus spp., Schonherri angus, Exopholis hypoleaca, Cylindera minuta, Bulenides spp., Borneola hijau, Borneola spp., Calomictus spp., Luperus spp., Ectamenogus spp., Anchastus spp., Lacon spp., Oxyropterus audoniwi, Colpodes spp., Carabus spp. 4 species of Cassinoidea, Dromius spp., Lebia spp., Stenolophus spp., Chlaenius spp., Heterotarsus spp., 2 species of Ceropria spp. 2 species of Plesiophthalmus, Episcapha maculate, Platypus cupulatus, Sternolophus, Acceraius laevicollis, Xyleborus foerstei, Bulenidea, Xyloberus and Stenochetus. With the moderate abundance and diversity of beetles on Langkawi Island, it is suggested that future land development in Langkawi be kept away from the forest reserves of Mt. Macincang and Mt. Gunungraya.